Long VITT: A case report. Issue 223 (March 2023) - Roberge, Guillaume; Carrier, Marc
Abstract: Vaccine-induced immune thrombotic thrombocytopenia (VITT) has been described following adenovirus vector-based COVID-19 vaccines. This condition is associated with important morbidity and mortality following thrombosis related complications. Diagnosis is confirmed based on results of platelet factor 4 ELISA detecting anti-PF4 antibodies and of platelet-activation assay. Initial treatment strategy has been established but long-term management and follow up remain unclear. Most platelet-activation tests become negative after 12 weeks. We describe a case of VITT which can now be characterized as long VITT. The patient initially had a lower limb ischemia, pulmonary embolism and cerebral vein thrombosis. He was treated with prednisone, intravenous immunoglobulin, argatroban and had a lower limb revascularization surgery. Rivaroxaban was then initiated for the acute treatment and continued for the secondary prevention of recurrent events. The patient still demonstrates positive platelet-activation tests and thrombocytopenia after more than 18 months of follow-up. No recurrent thrombosis or bleeding event have occurred. He is not known for any relevant past medical history other than alcohol consumption and slight thrombocytopenia (130 × 10 9 /L since 2015). It is unclear if the ongoing and more important thrombocytopenia could be explained by the persistent platelet-activating anti-PF4 antibodies or the patient's habits. Managing long VITT is challenging considering uncertainty regarding risks and benefits of long-term anticoagulation and potential needs of additional treatment. Additional data is needed to offer optimal long-term management for this patient population. We suggest that long VITT diagnosis definition might include the persistence within patient serum/plasma of anti-PF4 platelet-activating antibodies with clinical manifestations (e.g., thrombocytopenia) for more than 3 months. Highlights: Long-term management and follow up of VITT remain unclear. Persistence of platelet-activating anti-PF4 antibodies has been observed. Long VITT is challenging and needs to be defined.